MATHEMATICAL SPEECH AS A PRODUCTIVE FACTOR OF INFLUENCE ON THE SELF-EDUCATION OF STUDENTS OF IT-SPECIALTIES - Dubinina, Oksana (Physical and Mathematical Education, 2025)
Formulation of the problem. At present, when training IT specialists, higher engineering schools face the need to overcome the contradiction between the professionally demanded wide range of mathematical knowledge and skills for the above-mentioned specialists and the time limit for obtaining higher professional education. The relevance of the work is determined by the fact that the ability of modern specialists involved in the industrial production of software products to synthesize and competently use the mathematical apparatus in their professional activities depends on their mastery of the mathematical language as a universal information-storing, communicative, translational, integrating scientific knowledge tool for global application. The purpose of the presented study is to clarify the relationship and determine its extent between the state of students’ basic communicative qualities of mathematical speech and the results of their performance of purely professional tasks. Materials and methods. Processing of experimental data was carried out using correlation analysis. The basic communicative qualities of mathematical speech are described in the paper, and the author’s conceptual model of the implementation and functioning of the mathematical language through mathematical speech is proposed. The comparative analysis of the reduction of audience time allotted for the study of advanced maths sections for students of the Software Engineering specialty over the past 15 years has been conducted. Results. Enhanced studying of the mathematical language and development of mathematical speech of higher education graduates in the field of information and communication technologies contributes to the productive use of the potential of mathematics in order to intensify the educational process for the training of these specialists. Conclusions. Diagnostics of the state of basic communicative qualities of mathematical speech of future IT specialists showed that despite a fairly high passing score in mathematics when entering a higher technical educational institution, compared to other engineering specialties, 7.7% of students and 22.2% are at very low and low levels of these qualities, respectively. It is proven that this fact negatively affects the ability of higher education students to independently process technical and mathematical literature.